PENGARUH KETIDAKPASTIAN KEBIJAKAN EKONOMI AMERIKA SERIKAT, TIONGKOK, DAN JEPANG TERHADAP JAKARTA ISLAMIC INDEX - Maulidia Royhana; Titi Dewi Warninda (Jurnal Fokus Manajemen Bisnis, 2021)
This research aims to analyze the influence of United State Economic Policy Uncertainty, Tiongkok Economic Policy Uncertainty, and Japan Economic Policy Uncertainty on the Jakarta Islamic Index. This study used time-series data from January 2001 to December 2019 and Error Correction Model (ECM) to analyze the short-term and long-term effects of United State, Tiongkok and Japan Economic Policy Uncertainty on the Jakarta Islamic Index. The results of this research show that United State EPU and Tiongkok EPU have no short-term and long-term effect on Jakarta Islamic Index. Meanwhile, in the short-term, Japan EPU has a significant influence on the Jakarta Islamic Index but has no long-term influence.